2021
DOI: 10.1186/s12906-021-03437-5
|View full text |Cite
|
Sign up to set email alerts
|

Active constituent of Polygala tenuifolia attenuates cognitive deficits by rescuing hippocampal neurogenesis in APP/PS1 transgenic mice

Abstract: Background Alzheimer’s disease (AD) is the most common dementia worldwide, and there is still no satisfactory drug or therapeutic strategy. Polygala tenuifolia is a traditional Chinese medicine with multiple neuroprotective effects. In present study, we investigated the effects of three active constituents [3,6′-disinapoyl sucrose (DISS), onjisaponin B (OB) and tenuifolin (TEN)] of Polygala tenuifolia (PT) on the proliferation and differentiation of neural stem cells (NSCs) to identify the pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…The compound 3,6′-disinapoyl sucrose possesses the properties of anti-oxidative stress ( Shi et al, 2015 ; Tang X. et al, 2022 ), counteracting glutamate excitotoxicity ( Hu et al, 2014 ), enhancing neuroplasticity ( Hu et al, 2010 ), and promoting neurogenesis ( Wang et al, 2021 ). Therefore, it was frequently employed to treat conditions such as ischemic stroke, insomnia, amnesia, and depressive disorders.…”
Section: Q-marker Prediction Analysis Of Neuroprotective Effects Exer...mentioning
confidence: 99%
“…The compound 3,6′-disinapoyl sucrose possesses the properties of anti-oxidative stress ( Shi et al, 2015 ; Tang X. et al, 2022 ), counteracting glutamate excitotoxicity ( Hu et al, 2014 ), enhancing neuroplasticity ( Hu et al, 2010 ), and promoting neurogenesis ( Wang et al, 2021 ). Therefore, it was frequently employed to treat conditions such as ischemic stroke, insomnia, amnesia, and depressive disorders.…”
Section: Q-marker Prediction Analysis Of Neuroprotective Effects Exer...mentioning
confidence: 99%
“…Tenuigenin promotes the proliferation of neural stem cells and induces their differentiation into neurons and astrocytes ( Chen et al, 2012b ). Both onjisaponin B and tenuifolin enhance the proliferation of neural stem cells, though tenuifolin lacks the capability to facilitate migration and differentiation ( Wang et al, 2021 ), which are crucial for neurogenesis. In contrast, onjisaponin B promotes neural stem cell migration and induces their differentiation into astrocytes ( Wang et al, 2021 ).…”
Section: Pharmacological Effects Of Saponin Compoundsmentioning
confidence: 99%
“…Crossing the intestinal epithelial barrier and the BBB regulates hippocampal neural differentiation after EGCG interacts with the gut microbiota ( Faria et al., 2011 ; Granja et al., 2019 ). Qisheng Wan formula increased Bacteroidetes abundance in AD mice while reducing NF-κB, IL-6, and TNF-α content ( Xiong et al., 2022 ); one of its active ingredients, Polygala tenuifolia , promotes APP-NSCs proliferation and migration and neuronal differentiation ( Wang X. F. et al., 2021 ), while another ingredient, Acorus tatarinowii Schott , also affects neurogenesis, microglial function and can activate PKA-CREB signaling, enhancing nerve growth factor induced differentiation and neurite length of PC12 cells ( Cai et al., 2016 ; Lam et al., 2016 ). Lipopolysaccharide, amyloids, and other substances produced by Bacteroidetes affect neuroinflammation, possibly by regulating the brain inflammatory microenvironment to regulate neurogenesis ( Zhao and Lukiw, 2018 ), as confirmed by the effects of TCM presented above.…”
Section: Traditional Chinese Medicine Can Affect Neurogenesis By Regu...mentioning
confidence: 99%
“…Traditional Chinese medicine (TCM) is a medical system with a long history and is widely used in the prevention and treatment of nervous system diseases and regulation of body homeostasis. The active ingredients of TCM play an important role in regulating NSCs differentiation, and neuron and glia generation and activation ( Qin et al., 2017 ; Wang X. F. et al., 2021 ). Many reports have indicated that TCM can impact the composition and metabolism of the gut microbiota ( Feng et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%